2011
DOI: 10.1007/s00520-011-1340-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in high-grade glioma patients: a prospective single-center study

Abstract: We conclude that there were many changes in patients with high-grade glioma during the course of the disease and most of them were related to disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 39 publications
2
59
0
Order By: Relevance
“…The literature has identified differences in levels of anxiety, depression and HRQOL with respect to gender [68], age and KPS [10], while the role of tumor localisation is inconclusive [69][70][71]. Our study examined a limited number of relationships.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The literature has identified differences in levels of anxiety, depression and HRQOL with respect to gender [68], age and KPS [10], while the role of tumor localisation is inconclusive [69][70][71]. Our study examined a limited number of relationships.…”
Section: Study Limitationsmentioning
confidence: 99%
“…45 However, that study by Yavas et al excluded patients with KPS < 70, and baseline HRQoL was assessed after surgery. The latter is important as we demonstrate that surgery is the therapy most likely to induce sudden significant positive or negative changes in HRQoL.…”
Section: Deterioration In Hrqol After Tumor Progressionmentioning
confidence: 99%
“…Also, there are often strict inclusion criteria as part of oncological clinical trials, and patients with cognitive impairment 8 or patients with KPS scores less than 70 5,45 are often excluded. In the present study, we attempted to overcome these limitations.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Qualitative work told a story of suffering and struggle [40] in keeping with several quantitative studies which reported significant burdens particularly in psychosocial domains [37,38,44]. Other studies however found that self-reported quality of life was largely unaffected despite significant impairments in neuro-cognitive and functional domains [34,36,41,42].…”
Section: Patient Views Of Selfmentioning
confidence: 77%
“…Used as a means of coping, this phenomenon may contribute to positive quality of life assessments by patients in the face of poor functional health and well-being. [7, 34, 36-38, 41, 42, 44] Suffering and struggle persists amid multiple losses and future uncertainty [34,36,40] Anxiety, depression and distress are prevalent, particularly in the setting of disease progression, recurrence or poor functional outcomes [35][36][37][38][39]44] Neurocognitive and psychosocial deficits are perceived as more severe than patients' self-report [35,40] Patient quality of life is perceived as worse than caregiver quality of life [43] Caregiving is an ambiguous, relentless, exhausting task [40,43] Suffering and struggle persists amid multiple losses and future uncertainty [40] Caregiver quality of life is negatively impacted by poor patient neurocognitive and psychosocial function [43] Anxiety and depression are prevalent among caregivers [35,43] Caregiver anxiety may be independent of patient functional status [35] Caregivers have limited time for self-care and receive minimal external supports [43] J Neurooncol (2014) 120:1- 10 7 The two longitudinal studies found self-reported quality of life decreased with tumour recurrence and disease progression rather than duration of disease [34,44], although Lovely et al [40] found qualitative evidence that symptoms are progressive even in the absence of recurrence possibly due to late effects of treatment. Keir et al [39] showed that high rates of distress persist as patients transition into survivorship.…”
Section: Patient Views Of Selfmentioning
confidence: 99%